Benign endometriosis masquerading as intra-abdominal malignancy: One of the most extreme cases reported and a review of the literature. Issue 3 (September 2018) - Walker, Philippa J; Johnson, Neil P
Introduction: To elicit key clinical lessons from an extreme case of endometriosis associated with massive ascites and a review of the literature. Methods: We report one of the most extreme cases of massive ascites caused by endometriosis. For literature review, MEDLINE via OVID (from 1946 to 2016) database was searched. As a result, all the publications based on the keywords relating to the review topic were acquired. Case: A 32-year-old nulliparous woman, with stage 4 endometriosis and primary infertility, presented with massive ascites, complex pelvic mass, pleural effusion, weight loss, anaemia and elevated CA-125 suggesting ovarian malignancy. Six litres of ascites was drained. After extensive investigations to exclude malignancy, endometriosis-related ascites was diagnosed. Red-cell transfusion, nasogastric-tube-feeding and gonadotrophin-releasing-hormone analogue were initiated and long-term follow-up is planned. Ablation of ovarian function either by surgical oophorectomy or ovarian irradiation appears to cure the condition without recurrence. Endocrine therapy, in the form of gonadotrophin-releasing-hormone analogue or progestins, is useful if surgery is undesirable, as most women with this condition are young and wish to preserve fertility. Endocrine therapy alone resolves the problem in the majority, but ascites reappears after stopping treatment. Conclusion: Endometriosis associated with massive ascites and pleural effusion is rare. There are less than 30 similar case reports in the literature. In women of reproductive age who present with clinical and imaging features to suggest ovarian malignancy, a diagnosis of endometriosis should be considered. Although permanent cure is by oophorectomy, endocrine therapy is useful if surgery is undesirable.